GEL-MAN Hydrogel Loaded With Triamcinolone Acetonide for the Treatment of Osteoarthritis - Chen, Kai; Li, Shanzhu; Yuan, Feng; Sun, Pengfei; Zhang, Yingying (Frontiers in Bioengineering and Biotechnology, 2020)
One of the major challenges for the treatment of osteoarthritis (OA) with therapeutic drugs is the short half-life of drugs in the joint cavity. The severity of OA often fluctuates with time and inflammatory factors. Here, we describe the use of a hydrogel material, named Gel-Man, to solve the problem of rapid release of drugs. Gel-Man could encapsulate a series of therapeutic drugs and be degraded by hydrogen peroxide. It could be decomposed, and release drugs controlled by the concentration of hydrogen peroxide in the arthritic joint cavity. This hydrogel loaded with triamcinolone acetonide (TA) could slowly release the drug upon exposure to hydrogen peroxide in the joint cavity in patients suffering from osteoarthritis. The combination of TA and GEL-MAN hydrogels can slowdown the progression of degenerative change of osteoarthritis by maximizing the therapeutic efficacy and prolong the duration of drug treatment.